REDESIGN OF RANTAU PRAPAT TRAIN STATION - Sihombing, Sanggam Bonifasius; Lubis, Syamsulsyah; Wijaya, Michael Anderson (ASTONJADRO, 2021)
Along with the passage of time, the human need for modes of transportation is increasing. The increasing number of residents is inversely proportional to the limited time they have, so transportation modes such as trains are one solution. Rantau Prapat Railway Station has many shortcomings which of course must be improved and added to be able to serve the community in the future. This redesign is oriented to the community as users of transportation modes, how the flow of human and vehicle circulation is the main problem. The Rantau Prapat Railway Station must also be an attractive city gate, especially since the city of Rantau Prapat is the last destination city on the North Sumatra railway line. Therefore, the application of the Contextual Architecture theme is used so that the design that is set also follows the flow of an increasingly sophisticated future era. How a Railway Station that can function well functionally but can also be a city gate that gives interest to visit.